Analysis of Macro- and Microplastic Contaminations in Commercially Available Potting Soil Products - Emese Juhász; Gergely Zoltán Macher (Chemical Engineering Transactions)
Macro- and microplastics have emerged as pollutants in terrestrial ecosystems, yet limited knowledge exists regarding their presence in horticultural substrates. This paper employed qualitative and quantitative methods to analyse seven commercially available potting soil products. Fourier-transform infrared spectroscopy identified polyethylene, polypropylene, and polyamide as the dominant polymer types, with PE and PP accounting for over 65% of the detected plastics. Notably, particles measuring approximately 0.008 m were commonly observed, raising concerns about potential environmental accumulation. The paper also revealed significant variability in contamination levels across the samples, with S-2 and S-4 exhibiting the highest microplastic content, including the presence of blue and red synthetic fibres as observed microscopically. Additionally, signs of polymer degradation were detected through the identification of carbonyl peaks. These findings highlight a novel source of pollution within the consumer horticulture domain and provide new insights into plastic uptake pathways, potential risks to plant health, and the need for mitigation strategies to support sustainable agriculture. This work contributes to the growing understanding of microplastics in soil environments and may inform future environmental policy actions. Keywords: macroplastics, microplastics, potting soil, FT-IR, soil poll